Peningkatan Keterampilan Menulis Narasi Menggunakan Model Kooperatif Tipe Auditory, Intellectualy, Repetition di Kelas IV SDN 23 Kinali Kabupaten Pasaman Barat - Aflisia, Risa; Sukma, Elfia (Asian Journal of Early Childhood and Elementary Education, 2024)
This study aims to describe the improvement of students' narrative text writing skills using the Auditory, Intellectualy, Repetition Cooperative Model in class IV of SDN 23 Kinali, West Pasaman Regency. This study was conducted using the Auditory, Intellectualy, Repetition Cooperative Model in class IV of SDN 23 Kinali, West Pasaman Regency. The approaches used are qualitative and quantitative approaches. This type of research is Classroom Action Research (CAR) which is carried out in two cycles. Data collection techniques are in the form of observation, tests and non-tests. The results of the study showed an increase, in cycle I starting with the results of the analysis of the compilation: a) Teaching Modules showed an average of 82.5 (B) and cycle II became 95 (A), b) Implementation of teacher aspects in cycle I an average of 82.75 (B) and cycle II became 97 (A), while the implementation of student aspects in cycle I an average of 82.75 (B), and cycle II became 97 (A), c) Assessment of students' narrative writing skills in cycle I obtained an average of 76.5 (C) and cycle II an average of 93 (A). Based on these results, it can be concluded that the Auditory, Intellectualy, Repetition Cooperative Model can improve students' narrative writing skills in class IV SDN 23 Kinali, West Pasaman Regency.